A comparative study of Metallothionein gene expression in peripheral lymphocytes and blood cadmium level among die casting male workers - Ooi, Keok Loo; Adon, Mohd Yusoff; Cheah, Yoke Kqueen; Ismail, Patimah; Mat Jais, Abdul Manan (Canadian Center of Science and Education, 2010)
Cadmium were found in the die casting factory as by product of zinc alloy that used in the manufacturing of die cast. Metallothionein (MT) a carrier protein plays an important role in the detoxification process of cadmium in human. The usefulness of MT gene expression in peripheral blood lymphocytes (PBLs) as a biomarker of cadmium exposure and susceptibility could be determine by reverse transcriptase–polymerase chain reaction (RT-PCR). 41 male workers from die casting factory were involved in the cross-sectional comparative study and were divided into exposed and comparative group. MT gene expressions were found to proportionates increase with blood cadmium (BCd) levels. MT basal expression levels were significantly correlated with the BCd levels with r-value 0.616 for exposed group and 0.639 for comparative group. MT induction expression level were significant correlated with BCd level (r = 0.188 for exposed group, r = 0.342 for comparative group). This suggested that MT gene expression in PBLs can be used as a biomarker of susceptibility to cadmium.